Young Adults’ Experience of Loneliness in London’s Most Deprived Areas - Fardghassemi, Sam; Joffe, Helene (Frontiers in Psychology, 2021)
Young adults (16-24 years old) are currently the loneliest group in Western countries. In particular, young adults of lower socio-economic status living in the most deprived areas are loneliest in the UK. This mixed-methods study explored the experience of loneliness among this under-explored demographic in London. Using a novel free association technique, the experience of loneliness was found to be characterized by: a sense of isolation, negative emotions and thoughts, coping and a positive orientation to aloneness. An exploration of these themes revealed that: one can feel isolated or excluded even when surrounded by people; the experience of loneliness is accompanied by a set of interrelated feelings and thoughts like rumination; technological and/or non-technological outlets can be used to cope. Social media play both a positive and negative role in loneliness, and loneliness is not always experienced negatively. The quantitative data indicated that this sample was lonely. By providing insight into young adults’ loneliness, the findings indicate what types of interventions are likely to diminish it.